VD_FINDINFO HC / 2010 / 431 vom 21. Juni 2010 - VD Tribunal cantonal (2010)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE | 42 al. 1 CP, 47 CP, 415 CPP